Improvement of complex mechanization and automation of loading and unloading operations, when handling solid household waste - Tastemir Нурлан; Bulatov Нуржан; Menendez Pidal , Ignacio (Eurasian Journal of Applied Engineering and Technology (EJAET), 2024)
The relevance of this article is that, nowadays, waste generation has become a global problem. In the recent past, population growth has noticeably increased the rate of waste generation, and its disposal and management are a serious environmental problem worldwide. Waste management is understood as a set of measures for collection, sorting, transportation, with the use of effective complex mechanization and automation of loading and unloading operations. The purpose of this article is to study the most modern methods of complex mechanization and automation of loading and unloading operations during the collection, sorting and transportation of solid waste. The best method to study this problem is the analysis method, it makes it possible to explore the maximum number of sources to provide the best results. The article examines the latest achievements in this field, such as automation methods, geographic information system and GPS, remote sensing, system engineering methods, the pneumatic waste transportation system most used in developed countries, and also proposes a model of a new garbage chute for multi-storey, high-rise residential and public buildings. The analysis showed that GPS applications were mainly used to track garbage cans and garbage collection vehicles to monitor the time and place of collection. GPS and GIS methods work better together than separately. And the pneumatic waste transportation system has a number of significant drawbacks that can be corrected by using a new model of a garbage chute for multi-storey, high-rise residential and public buildings.